Microbial quality of water in rural households of Ethiopia: Implications for milk safety and public health - Amenu, K.; Spengler, M.; Markemann, A.; Zarate, A.V. (2014)
Waterborne pathogenic agents affect the health of people either by direct consumption of contaminated water or by its indirect use in food production and/or processing. Studies on the microbiological quality of water in rural areas of Ethiopia are still limited, especially at the household level. The aim of the present study was to assess the microbial quality of water from different sources in rural households in two districts of the Ethiopian Rift Valley area. The correlation between E. coli counts in water and milk was also investigated. In total, 233 water samples (126 collected in dry and 107 in wet season) and 53 milk samples (19 from raw milk and 36 from processed milk products) were analyzed for E. coli contamination. The overall prevalence of E. coli in water samples was 54.9% (n=233). In most of the analyzed samples, a higher prevalence of E. coli was recorded during the wet compared to the dry season. The highest load of E. coli was detected in water samples from dugouts. The quality of raw milk and traditionally-processed milk products showed variations between districts, and the traditionally-processed milk products were found to contain higher E. coli loads than raw milk. The correlation between the E. coli counts in water and milk only showed a weak but positive relationship (r =0.1). Taking E. coli as a proxy for water quality, the microbiological quality of water consumed in the study area was found to be very poor, posing a potential food safety and health risk to the rural communities.